The Analysis of Students’ Problem-Solving Skills About Temperature and Heat - Anderias Henukh; I Made Astra; Selestina Kostaria Jua; Aay Susilawati (Postgraduate, University of Mataram, 2024)
This journal reviews students' problem-solving skills after participating in a problem-solving-based learning process. This study aims to determine the student's problem-solving skills and social students who follow a cross-interest program in physics. The study utilized a quantitative approach with descriptive methods and a one-group pretest-posttest research design. The research subjects were 29 students in class X Social 4 at SMAN Sambungmacan, Sragen. In this study, students were asked to complete four question descriptions after studying temperature and heat material. Student problem-solving results were analyzed using a point system. The average and percentage of student achievement were calculated for each problem and its stages of problem-solving. Analysis of problem-solving skills data revealed that the average percentage of students' problem-solving skills reached 65.3%. Based on data analysis and results, all students' problem-solving abilities have improved since the pretest. It is hoped that students will continue to be accustomed to solving problems using the stages of problem-solving in the future.